2021
DOI: 10.33899/magrj.2021.129557.1117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Freeze Storage on the Quality of Lamb Meat Treated With Tomato Peel and Sumac Extracts

Abstract: The study was conducted to investigate the influence of natural antioxidants extracted from tomato (Solanum lycopersicum) peel extract (TPE) and sumac (Rhus coriaria) extract (SE) on the quality of lamb meat stored for (6) months at freezestorage (-18 °C). Treated samples (TS) with these extracts showed a significant values (p<0.05) of drip loss and water holding capacity (WHC) compared to untreated samples (UTS). The UTS demonstrated a significant increase (p≤0.05) of cooking loss values compared to TS. Perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…Similarly, [20] they found that cooking loss of sheep meat feeding on diets supplemented with herbals was higher than control feeding group. Regards to storage conditions, the changes in cooking loss are consistency with results of Sadallah and Khalil [29] they found that cooking loss of all the lamb samples significantly increased after 30 days of frozen storage after that the reduction in cooking loss was small and not significant till the end of storage period.…”
Section: Cooking Losssupporting
confidence: 87%
“…Similarly, [20] they found that cooking loss of sheep meat feeding on diets supplemented with herbals was higher than control feeding group. Regards to storage conditions, the changes in cooking loss are consistency with results of Sadallah and Khalil [29] they found that cooking loss of all the lamb samples significantly increased after 30 days of frozen storage after that the reduction in cooking loss was small and not significant till the end of storage period.…”
Section: Cooking Losssupporting
confidence: 87%